SPE Annual Technical Conference and Exhibition 1983
DOI: 10.2118/12118-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study of the Effects of Hydraulics on Hole Erosion

Abstract: Laboratory studies were made with fluids contai ni ng bentonite and mi croce 11 ul ose fi bers to determine the relationship of rheological variables to borehole erosion. The primary objective of the study was to observe hole erosion that results from purely hydraul ic effects. The study was made by Circulating fluid through a hole in a specimen made of compacted ground shale.The results of the investigation show a relationship between erosion, fluid wall shear stress, and plastic Reynolds number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…1) and may thus be related to the rock anisotropy (Table 2). Babcock, 1978Guenot, 1989Brown, 1978Schafer, 1980 Hubbert andWillis, 1957;Haimson and Fairhurst, 1967;Haimson, 1978Morin et al, 1990Guenot, 1987Dart and Zoback, 1989Hottman et al, 1979Bell and Gough, 1979;Zoback et al, 1985Guenot, 1989Cheatham, 1984Teufel, 1983;Bradley, 1979Babcock, 1978Dart andZoback, 1989 Plumb andCox, 1987;Plumb and Hickman, 1985Guenot, 1989Gaylord, 1983 Table 1) and azimuth (AzCmax) of the pad that corresponds to the larger measured diameter for each of the five passes, labeled from pi to p5. Azimuth is with respect to magnetic north.…”
Section: Discussionmentioning
confidence: 99%
“…1) and may thus be related to the rock anisotropy (Table 2). Babcock, 1978Guenot, 1989Brown, 1978Schafer, 1980 Hubbert andWillis, 1957;Haimson and Fairhurst, 1967;Haimson, 1978Morin et al, 1990Guenot, 1987Dart and Zoback, 1989Hottman et al, 1979Bell and Gough, 1979;Zoback et al, 1985Guenot, 1989Cheatham, 1984Teufel, 1983;Bradley, 1979Babcock, 1978Dart andZoback, 1989 Plumb andCox, 1987;Plumb and Hickman, 1985Guenot, 1989Gaylord, 1983 Table 1) and azimuth (AzCmax) of the pad that corresponds to the larger measured diameter for each of the five passes, labeled from pi to p5. Azimuth is with respect to magnetic north.…”
Section: Discussionmentioning
confidence: 99%
“…Kamphuis and Hall (1983) investigated the erosion of cohesive materials by unidirectional currents. Rocha also describes similar work by Gaylord (1983) on erosional effects of fluid flow on clay-containing materials. Gaylord (1983) showed that erosion first increases slowly with increasing fluid velocity and then increases rapidly after some critical velocity is reached.…”
Section: Coal Gas Production and Other Erosion Researchmentioning
confidence: 91%
“…Rocha also describes similar work by Gaylord (1983) on erosional effects of fluid flow on clay-containing materials. Gaylord (1983) showed that erosion first increases slowly with increasing fluid velocity and then increases rapidly after some critical velocity is reached. Further work may be warranted to address the implications of these studies.…”
Section: Coal Gas Production and Other Erosion Researchmentioning
confidence: 91%